1997
DOI: 10.4141/a97-013
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chronic parenteral pyridoxine and acute enteric tryptophan on pyridoxine status, glycemia and insulinemia stimulated by enteric glucose in weanling piglets

Abstract: Matte, J. J., Ponter, A. A. and Sève, B. 1997. Effects of chronic parenteral pyridoxine and acute enteric tryptophan on pyridoxine status, glycemia and insulinemia stimulated by enteric glucose in weanling piglets. Can J. Anim. Sci. 77: 663-668. In order to investigate the importance of the relation between pyridoxine and tryptophan on glucose tolerance and insulin response to glucose, 12 Large White × Pietrain piglets (males and females), weaned at 3 wk of age, were allocated to two treatment groups. Within e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 16 publications
1
24
1
Order By: Relevance
“…Effect of dietary tryptophan on the response of insulin and gastric inhibitory peptide (GIP) measured after meal in piglets (Ponter et al, 1994a); for individual time points, ⁎⁎⁎ designs statistical difference between low and control Trp at P b 0.001. plasma insulin when a physiological level of tryptophan was associated to a glucose load (Ponter et al, 1994a). Further results confirmed that supplemental tryptophan could help preventing this insulin resistance status in pigs under the condition of an adequate vitamin B6 status (Matte et al, 1997). Recently Zhang et al (2007) suggested that, in pigs, tryptophan effect on appetite could be mediated by ghrelin, a gut hormone involved in the regulation of food intake.…”
Section: Tryptophan Effect On Appetitementioning
confidence: 81%
“…Effect of dietary tryptophan on the response of insulin and gastric inhibitory peptide (GIP) measured after meal in piglets (Ponter et al, 1994a); for individual time points, ⁎⁎⁎ designs statistical difference between low and control Trp at P b 0.001. plasma insulin when a physiological level of tryptophan was associated to a glucose load (Ponter et al, 1994a). Further results confirmed that supplemental tryptophan could help preventing this insulin resistance status in pigs under the condition of an adequate vitamin B6 status (Matte et al, 1997). Recently Zhang et al (2007) suggested that, in pigs, tryptophan effect on appetite could be mediated by ghrelin, a gut hormone involved in the regulation of food intake.…”
Section: Tryptophan Effect On Appetitementioning
confidence: 81%
“…Measurements of Se were done using a fluorimetric method adapted by Giguère et al (2005) from the technique of Sheehan & Gao (1990) and P-5-P was determined using a fluorimetric method adapted by Matte et al (1997) from the technique of Srivastava & Beutler (1973). SeGPX activity was determined in blood plasma by the spectrophotometric method described by Gunzler & Flohe (1985).…”
Section: Laboratory Analysismentioning
confidence: 99%
“…The 3 forms of vitamin B 6 , pyridoxamine (PAM), pyridoxal (PAL), and pyridoxine (PYR), were determined in duplicate by adaptation of methods described by Srivastava and Beutler (1973) and Matte et al (1997). Four stock solutions made in ultrapure water (500 μg/mL; Sigma-Aldrich) of PAM, PAL, PYR, and pyridoxal-5 -phosphate (P5P) were diluted (one-tenth for PAM, PAL, and P5P; one-thirtieth for PYR) to obtain standard solutions (respectively, 207, 246, 202, and 81 μM).…”
Section: Niacin (B3)mentioning
confidence: 99%